The Level of Passion for Knowledge among High School Students while Learning Social Studies in Saudi Arabia - Najmuldeen, Hanan A (Asian Journal of Education and Training, 2021)
The present research paper aims to measure the level of passion for knowledge while learning social studies among high school students in Saudi Arabia. It adopts a descriptive approach. To achieve its objectives, the researcher created a scale of passion for knowledge that consists of 25 sentences. The study population covered all high school students in Jeddah, but the scale was applied to a stratified sample of 1142 students only who were selected randomly from all the public high schools in Jeddah, Saudi Arabia. The results show that the level of passion for knowledge is high as it reached 3.77. Compared with the other grades, the highest level of passion for knowledge was found for the first-grade high school students because they studied the new curricula in all stages, while those in the second and third grades studied the curriculum that was implemented before curricula were developed according to Saudi Vision 2030.